Effect of variations in drying temperature of papaya seeds (Carica papaya L.) on the physiochemical characteristics of jelly candy - Utomo, Rizki Aldhianto; Rahmadhia, Safinta Nurindra (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2024)
Papaya seeds contain various phenolic compounds, such as flavonoids, which act as antioxidants. However, papaya seeds have a tart taste and pungent odor caused by benzyl isothiocyanate compounds. The drying process of papaya seeds can reduce the tartness and fragrant odor of papaya seeds. This study aimed to evaluate of different drying temperatures on the physicochemical and organoleptic characteristics of jelly candy made from papaya seeds.. This study used three drying temperatures: 50 °C (F1), 60 °C (F2), and 70 °C (F3). After drying, the papaya seeds are powdered and processed into jelly candy. Jelly candy was prepared by adding jelly powder and gelatin to achieve the desired texture. The physicochemical analysis included measurements of water content, ash content, pH, antioxidants, flavonoids, and texture, while organoleptic evaluations assessed sensory properties. Statistical analysis was performed using one-way ANOVA. The results showed no significant decrease in water content (14.59%–15.58%), while pH (4.7–4.9), antioxidant activity (4.44%–24.03%), and total flavonoid content (4.31–8.09 mgQE/g) decreased. Ash content significantly increased (0.37%–0.40%). The physical properties analysis showed hardness values of 133.17–151.89 N, gumminess of 33.03–51.70 N, and chewiness of 21.07–36.44 N. Organoleptic analysis revealed that panelists most favored sample F3.